Aflatoxin contamination of animal feeds and its predictors among dairy farms in Northwest Ethiopia: One Health approach implications - Tadele, Fitalew; Demissie, Biruk; Amsalu, Alebachew; Demelash, Habtamu; Mengist, Zelalem; Ambelu, Argaw; Yenew, Chalachew (Frontiers in Veterinary Science, 2023)
Background In dairy farming, animal feed is the first line of food safety. Animal feed can become contaminated and spoiled on farms or in storage facilities due to the diverse microorganisms that are naturally present around or on various animal feeds. This study aims to assess the level of aflatoxin and predictors in animal feeds among dairy farms in the South Gondar Zone of Ethiopia. Methods A total of 100 samples of each animal feed ingredient (atella, hay, commercial concentrates, and cut and carry pasture) were obtained. A total of 400 animal feed ingredient samples were tested separately among 100 randomly chosen dairy farmers for aflatoxin analysis. Simultaneously, swabs from cow udders and water samples were also collected. Using a structured and pretested questionnaire, the knowledge and practices of animal feed administrators responsible for managing animal feed were also evaluated. Descriptive statistics and logistic regression models were used to identify determinants. Results From the total animal feed analyzed, 96% was positive for aflatoxins. Feed storage facilities, feed storage duration, education of animal feed administrators, mixed concentrates, and previous training were found to be associated with aflatoxin contamination levels in animal feeds. Conclusions The levels of aflatoxin contamination in animal feeds were found to be higher than the recommended limit; these findings suggest the spread of aflatoxin contamination between humans and animals. Furthermore, the occurrence of aflatoxins in the environment results from milk becoming contaminated with aflatoxins. A One Health strategy should therefore receive special consideration to tackle such problems and safeguard consumer safety.